1996
DOI: 10.1007/bf00033090
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation for saturated fatty acid content in soybean

Abstract: Concern over high saturates in human diets has prompted the development of soybean [Glycine max (L.) Merr .] lines producing oil with reduced saturated fatty acid concentration . To better understand those factors that influence phenotypic expression for palmitic and stearic acid content in soybean, thirty soybean lines random for saturated fatty acid content were grown in eight field environments contrasting for mean temperature during seed-filling .Palmitic and stearic acid content varied significantly (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
7
25
1
Order By: Relevance
“…In soybean, however, studies on temperature or CO 2 effects on seeds have not yet been associated with expression of specific genes related to seed storage compounds. The ratio of polyunsaturated to monounsaturated fatty acids in soybean oil is known to decrease with high temperature (Rebetzke et al 1996;Wolf et al 1982); however, the abundance of transcripts encoding fatty acid desaturase did not change (Heppard et al 1996). Tomas et al (2003) observed substantial differences in seed composition due to growth temperatures for plants grown at temperatures increasing from 28/18 to 44/34°C and there was no effect due to elevated CO 2 level.…”
Section: Ricementioning
confidence: 88%
See 1 more Smart Citation
“…In soybean, however, studies on temperature or CO 2 effects on seeds have not yet been associated with expression of specific genes related to seed storage compounds. The ratio of polyunsaturated to monounsaturated fatty acids in soybean oil is known to decrease with high temperature (Rebetzke et al 1996;Wolf et al 1982); however, the abundance of transcripts encoding fatty acid desaturase did not change (Heppard et al 1996). Tomas et al (2003) observed substantial differences in seed composition due to growth temperatures for plants grown at temperatures increasing from 28/18 to 44/34°C and there was no effect due to elevated CO 2 level.…”
Section: Ricementioning
confidence: 88%
“…In addition to changes in the concentration of oil produced in seeds, the ratio of fatty acids in soybean oil changes when seeds develop under elevated temperature. For example, oleic acid concentration increased with increasing temperatures while linoleic acid decreased (Carver et al 1986;Rennie and Tanner 1989;Rebetzke et al 1996). Heagle et al (1998) observed a positive, significant effect of CO 2 enrichment on soybean seed oil and oleic acid concentration.…”
Section: Ricementioning
confidence: 96%
“…However, our results were contrary to the findings of Were et al, [28] who found that an increase in palmitic acid was accompanied with an increase in both stearic and oleic acids in sesame. Meanwhile, studies on peanut [29] and soybean [30] revealed negative correlation between palmitic and oleic acid. This different relationship may be due to species-specific factors.…”
Section: Crude Fat Content Fatty Acid Composition Of Castor Varietiesmentioning
confidence: 99%
“…This relationship was contrary to the findings in peanut [29] and soybean. [30] Thus, it could be speculated that the interrelationship between different enzymatic steps of fatty acid synthesis is the main determinant of the fatty acid composition in castor seeds. [28] …”
Section: Crude Fat Content Fatty Acid Composition Of Castor Varietiesmentioning
confidence: 99%
“…14 Therefore it is important to undertake systematic characterization of the available gene pool for its variable fatty acid profile to be utilized for specific purposes. The surveys of fatty acid composition in the international germplasm of soybean, 15 sunflower, 12 maize 16 and rapeseed-mustard 17 have revealed wide variation in the proportion of the different fatty acids, offering possibilities of developing superior quality edible oils and specialized industrial oils. 18 -20 A survey of fatty acid composition of Ethiopian mustard would be useful to identify land races of different seed oil compositions to breed varieties with better yield and superior quality edible oil for niche markets.…”
Section: Introductionmentioning
confidence: 99%